Pengaruh Penggunaan Media Ispring Terhadap Hasil Belajar Biologi Siswa Kelas X SMA Negeri 9 Bone Kabupaten Bone - Wahyuni, Sri (Universitas Negeri Makassar, 2020)
Abstract. The purpose of this study is to know determine the effect of using Ispring media on biology learning outcomes of class X SMA Negeri 9 Bone at Bone regency. The type of research is quasy experiment using Posttest Only-Non-Equivalent Control Group Design. The sampling technique was purposive sampling. Subject of this research consisted of 2 group namely control class (powerpoint media) of 28 student and experimental class (Ispring media) of 30 student. The variabel examine in this study were Ispring media and powerpoint media. Technique of data collection was form test and analysis using descriptive analysis and inferential analysis. The result showed that the average value of learning outcomes of biology using powerpoint media was 80,36 and the average value student using Ispring media was 84,17. Based on inferential analysis using the t test that the value Sig. (2-tailed) sebesar 0,029 < 0,05, then H0 rejected and Ha was accepted. It can be concluded that there is an effect of using Ispring media on biology learning outcomes of class X SMA Negeri 9 Bone at Bone regency. Keywords: Ispring media, learning outcomes